2019
DOI: 10.1111/mpp.12880
|View full text |Cite
|
Sign up to set email alerts
|

The effector GpRbp‐1 of Globodera pallida targets a nuclear HECT E3 ubiquitin ligase to modulate gene expression in the host

Abstract: Summary Plant‐parasitic nematodes secrete effectors that manipulate plant cell morphology and physiology to achieve host invasion and establish permanent feeding sites. Effectors from the highly expanded SPRYSEC (SPRY domain with a signal peptide for secretion) family in potato cyst nematodes have been implicated in activation and suppression of plant immunity, but the mechanisms underlying these activities remain largely unexplored. To study the host mechanisms used by SPRYSEC effectors, we identified plant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…Several studies have shown that at least some of the SPRYSEC proteins suppress effector‐triggered immunity (ETI) induced by the activation of resistance proteins (Ali, Magne, Chen, Obradovic et al, 2015; Mei et al., 2015; Postma et al., 2012). More recently it has been shown that one SPRYSEC targets the plant ubiquitination machinery to modulate stress responses (Diaz‐Granados et al., 2020). Although a role for SPRYSECs in suppressing host defence responses has been established, there are many questions remaining about this gene family.…”
Section: Effectors Of Pcnmentioning
confidence: 99%
“…Several studies have shown that at least some of the SPRYSEC proteins suppress effector‐triggered immunity (ETI) induced by the activation of resistance proteins (Ali, Magne, Chen, Obradovic et al, 2015; Mei et al., 2015; Postma et al., 2012). More recently it has been shown that one SPRYSEC targets the plant ubiquitination machinery to modulate stress responses (Diaz‐Granados et al., 2020). Although a role for SPRYSECs in suppressing host defence responses has been established, there are many questions remaining about this gene family.…”
Section: Effectors Of Pcnmentioning
confidence: 99%
“…In M. oryzae , effectors are delivered to the cytosol through a specific structure called the biotrophic interfacial complex (BIC) (Khang et al, 2010 ). Most of the effectors from pathogens contribute quantitatively to pathogen aggressiveness, but some of them, such as Cmu1 and Scc1 in Ustilago maydis (Djamei et al, 2011 ; Redkar et al, 2015 ), BAS107 in M. oryzae (Giraldo et al, 2013 ), MiSSP7 in Laccaria bicolor , which functions as a negative regulator of jasmonic acid (JA)‐induced gene regulation in the nucleus (Plett et al, 2011 ), PcCRN4 in Phytophthora capsici , which suppresses host defence and induces cell death in the plant nucleus (Mafurah et al, 2015 ), SsSSVP1 in Sclerotinia sclerotiorum (Lyu et al, 2016 ), VdSCP7 in Verticillium dahliae (Zhang et al, 2017 ), and SCRE1 in Ustilaginoidea virens , which inhibits host immunity and suppresses the immunity‐associated hypersensitive response (HR) via the plant nucleus (Zhang, Yang, et al, 2020 ), have been identified as potential nuclear‐localized regulators of the host cell targeting process (Diaz‐Granados et al, 2020 ). The conserved targeting mechanism of a common host protein network for convergent effectors from the eubacteria Pseudomonas syringae , the oomycete Hyaloperonospora arabidopsidis , and the ascomycete Golovinomyces orontii has been explored in the model plant species Arabidopsis thaliana (Weßling et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that the HECT gene family influences ATP binding, isopeptidase activity, histone binding, protease activity, and numerous molecular and biological processes in tomato. The HECT E3 ubiquitin ligases have been identified to regulate trichome development 54 , leaf senescence 55 , biotic stress 56 , cell growth, proliferation, autophagy, DNA repair, antiviral responses, and many diseases 40 . Our results agree with previous studies and predict extended involvement in the tomato cellular and genetic processes.…”
Section: Discussionmentioning
confidence: 99%